The Relative Contribution of Resilience and Social Support to Family Quality of Life of a Sample of Mothers of Children with Autism Spectrum Disorder in Qatar - AL-Dalaeen, Anas Saleh (Dirasat: Educational Sciences, 2022)
Objectives: This study aimed to identify the level of communicative apprehension and psychological loneliness, and to verify the relative contribution of the elements of communicative apprehension to psychological loneliness among the elderly recovering from the (Covid-19) virus in Jordan, and to identify the difference in communicative apprehension and psychological loneliness according to gender. Methods: To achieve the objectives of the study, the study was conducted on an available sample of 158 elderly recovering from the (Covid-19). The descriptive relational analytical method was used by sending the link to several groups through the convenience sampling. The communicative obsessiveness scale was also developed, relying on the Obeid scale (Obeid, 2010) of psychological loneliness in the elderly, and the psychometric properties of the two scales were verified for validity and reliability. Results: The results showed that there is a medium level of communicative apprehension, and a high level of psychological loneliness, and that the dimensions of communicative apprehension predict an amount of (27%) of psychological loneliness, and that communicative apprehension is higher in males than in females. Based on the results of the study. Conclusions: The factors associated with communication apprehension and psychological loneliness in the elderly should be known, by studying different demographic variables.